2012
DOI: 10.1093/protein/gzs026
|View full text |Cite
|
Sign up to set email alerts
|

Identification of beta-amyloid-binding sites on transthyretin

Abstract: Transthyretin (TTR) binds to the Alzheimer-related peptide beta-amyloid (Aβ), and may protect against Aβ-induced neurotoxicity. In this work, the specific domains on TTR involved with binding to Aβ were probed. An array was constructed of peptides derived from overlapping sequences from TTR. Strong binding of Aβ to TIAALLSPYSYS (residues 106-117) was detected, corresponding to strand G on the inner β-sheet of TTR. Aβ bound weakly to four contiguous peptides spanning residues 59-83, which includes strand E thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(104 citation statements)
references
References 44 publications
7
95
0
Order By: Relevance
“…Our estimation of the K D differs substantially from previously estimated binding parameters of K S at 2300 M Ϫ1 (Liu and Murphy, 2006) by tryptophan fluorescence quenching and K D of 28 nM using competition binding (Costa et al, 2008b). Our NMR data showed that the A␤ binding site on TTR involves amino acids in and around the T 4 binding site of the tetramer, partially confirming and extending the recently reported involvement of TTR residues L17, L110, and L82 (but S85) (Du et al, 2012;Yang et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our estimation of the K D differs substantially from previously estimated binding parameters of K S at 2300 M Ϫ1 (Liu and Murphy, 2006) by tryptophan fluorescence quenching and K D of 28 nM using competition binding (Costa et al, 2008b). Our NMR data showed that the A␤ binding site on TTR involves amino acids in and around the T 4 binding site of the tetramer, partially confirming and extending the recently reported involvement of TTR residues L17, L110, and L82 (but S85) (Du et al, 2012;Yang et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Experiments showing reduced inhibition of A␤ aggregation when the T 4 site is occupied by small molecules confirm its involvement in A␤ binding. These results are consistent with, but more definitive than, previous data from cross-linking experiments, alanine scanning mutagenesis, and peptide inhibition of TTR-A␤ interaction, which suggested major roles for residues L110 in strand G and L82 in the EF helix/loop in binding A␤ (Du et al, 2012;Yang et al, 2013). Our data suggest that L82, rather than serving as an A␤ oligomer sensor (Yang et al, 2013), may influence the orientation of the side chain of W79, which usually points to the T 4 binding site.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…TTR appears to be a major A␤-sequestering protein in human CSF, inhibiting and even reverting the formation of amyloid fibrils, as well as reducing their toxicity in vitro (58,59). TTR forms a complex with A␤ monomers/dimers, with stronger binding affinity observed for the more structurally flexible S85A TTR mutant (60), reinforcing the idea that less structured forms of amyloid proteins may be more likely to engage in cross-amyloid interactions.…”
Section: Transthyretinmentioning
confidence: 78%
“…Interestingly a recent account suggested that β-amyloid binds to TTR; however, it appears that the interaction occurs after tetramer dissociation. 14 We are interested in the development of broad-spectrum inhibitors of amyloid formation. The trpzip peptides are among the smallest β-hairpin peptides known to fold spontaneously without the use of disulfide-bonds or metal ions.…”
mentioning
confidence: 99%